MANAJEMEN KEUANGAN BAGI LEMBAGA SWADAYA MASYARAKAT SESUAI DENGAN ISAK 35 DI INSTITUT SOLIDARITAS BURUH SURABAYA (ISBS) - Susliyanti, Eni Dwi; Affan, Junaidi; Attalah, Ananda Haikal; Sukatni, Sukatni (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The problem faced by ISBS NGOs is that they do not have financial reports in accordance with the latest regulations. The benefits obtained by ISBS NGOs from community service activities are having updated financial SOP documents and financial reports in accordance with applicable regulations, namely ISAK 35. Methods used in community service activities include: online socialization and coordination of ISBS service activities, making proposals activities and letters from service partners, reading and studying financial SOP documents and ISBS Financial Reports, as well as Technical Assistance Financial SOPs and financial reports in accordance with ISAK 35. The results of community service activities include updating financial SOP documents in accordance with the latest regulations. Apart from that, the financial reports produced are also in accordance with ISAK 35